EVALUASI KINERJA METODE ANALYTICAL HIERARCHY PROCESS (AHP) DALAM PENELUSURAN ASET PADA LINGKUNGAN BISNIS STUDI KASUS PADA INDUSTRI PERBANKAN - Isworo Nugroho (Yayasan Grace Berkat Anugerah, 2024)
Asset tracing is an important activity in business management, especially in the banking industry where asset management has direct implications for a company's financial health and sustainability. In this context, this study aims to evaluate the performance of the Analytical Hierarchy Process (AHP) method in asset tracing, with case studies in the banking industry. This study adopts a quantitative approach by applying AHP in selecting asset tracing priorities in the banking business environment. Asset-related data, such as value, risk, and strategic importance, are collected and analyzed to support the decision-making process. Furthermore, AHP is applied to determine the relative weighting of the relevant criteria and generate a rating for each asset based on the assessment of those criteria. The results of the performance evaluation of the AHP method in asset tracing in the banking industry show that this approach provides a systematic and structured framework for decision making. By using AHP, asset ratings can be determined more objectively and transparently, reducing the risk of errors and misappropriations in resource allocation. In addition, AHP allows management to prioritize asset tracing based on the company's business objectives and strategic needs. In conclusion, the performance evaluation of the AHP method in asset tracing in the business environment, especially in the banking industry, shows the potential to improve the efficiency and effectiveness of asset management. With a structured, data-driven approach like AHP, companies can optimize resource usage and reduce the risk of loss caused by assets that are not strategically optimized.